Electrolyte membrane sheet strip and method for manufacturing same

By using an electrolyte membrane with a thickness of 40 μm or more during the electrolyte membrane manufacturing process, and adjusting the structure and coating steps of the membrane, the problems of catalyst ink overflow and ridges of the membrane edges are solved, ensuring the stability of the membrane and the smooth progress of subsequent processing.

JP7669877B2Active Publication Date: 2025-04-30TORAY INDUSTRIES INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021136938
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-25
Publication Date
2025-04-30
Estimated Expiration
2041-08-25

AI Technical Summary

Technical Problem

During the process of manufacturing the electrolyte diaphragm tape, the catalyst ink is prone to overflow when applying the catalytic layer, contaminating peripheral equipment, and electrolyte diaphragms with larger thickness may have edge bulges after cutting, affecting subsequent processing.

Method used

An electrolyte membrane with 40 μm or more is adopted, and the membrane consists of a substrate, a first electrolyte layer, a composite layer containing a pore matrix and a second electrolyte layer. The wide end position of the second electrolyte layer is located inside the wide end position of the substrate, the first electrolyte layer and the composite layer. By adjusting the coating and drying steps, the thickness of the second electrolyte layer is ensured to prevent the catalyst ink from overflowing.

Benefits of technology

Effectively prevent the catalyst ink from overflowing when the catalytic layer is applied, and prevent the electrolyte diaphragm from raising its edges after cutting, thereby ensuring the smooth progress of subsequent processing steps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669877000005
    Figure 0007669877000005
  • Figure 0007669877000006
    Figure 0007669877000006
  • Figure 0007669877000007
    Figure 0007669877000007
Patent Text Reader

Abstract

To provide a belt-like object of an electrolyte membrane sheet, capable of appropriately executing a lamination step of a catalyst layer.SOLUTION: In a belt-like object of an electrolyte membrane sheet, in which an electrolyte membrane is laminated on a belt-like material film, a thickness of the electrolyte membrane is 40 μm or more, and the electrolyte membrane includes: a first electrolyte layer containing a high polymer electrolyte in order from the material film; and a second electrolyte layer containing a composite layer including a porous base and the high polymer electrolyte and the high polymer electrolyte. In the belt-like object of the electrolyte membrane sheet, the material film and both end parts of the first electrolyte layer and the width direction of the composite layer are positioned at the same position, and each of both end parts of the width direction of the second electrolyte layer is existed in the side inner from both end parts of the width direction of any one of the material film, the first electrolyte layer, and the composite layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a strip of an electrolyte membrane sheet and a method for producing the same. [Background technology]

[0002] In recent years, hydrogen energy has been attracting attention as a next-generation means of energy storage and transportation. When used as fuel for fuel cells, hydrogen can theoretically be converted into electricity with higher energy efficiency than power generation using heat engines, and since it produces no harmful emissions, it has the potential to be a highly efficient clean energy source.

[0003] Hydrogen is a secondary energy source that can be produced in a variety of ways, but if surplus electricity from renewable energy sources is used to electrolyze water, it is possible to convert electricity into hydrogen energy without emitting carbon dioxide. Methods for producing hydrogen through water electrolysis include alkaline water electrolysis and polymer electrolyte membrane (PEM) water electrolysis. PEM water electrolysis can be operated at high current density, and has the advantage of being able to flexibly respond to fluctuations in renewable energy output.

[0004] In PEM-type water electrolysis hydrogen generation devices, it is necessary to prevent the generated hydrogen from permeating back from the cathode to the anode, and it has been proposed to use an electrolyte membrane with a relatively large thickness in order to improve the hydrogen barrier properties (for example, see Patent Document 1).

[0005] On the other hand, it is known that a porous substrate (reinforcing material) is disposed inside the electrolyte membrane to enhance the durability of the polymer electrolyte membrane. A composite electrolyte membrane containing such a porous substrate is known to have an electrolyte layer made of a polymer electrolyte on each side of a composite layer in which a porous substrate is filled with the polymer electrolyte.

[0006] As a method for producing the above-mentioned composite electrolyte membrane, for example, a method has been proposed in which an electrolyte solution is applied to a long strip-shaped substrate film, a porous substrate is placed on top of the substrate and impregnated with the electrolyte solution, and then the electrolyte solution is applied to the other surface of the porous substrate (see, for example, Patent Documents 2 and 3).

[0007] A catalyst layer is continuously laminated on the strip of electrolyte membrane sheet produced as described above to produce an electrolyte membrane with a catalyst layer, and a gas diffusion electrode is further laminated on the strip to produce a membrane-electrode assembly, which is then used in fuel cells, water electrolysis hydrogen generation devices, etc. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2016-216826 A [Patent Document 2] JP 2015-76201 A [Patent Document 3] JP 2019-186183 A Summary of the Invention [Problem to be solved by the invention]

[0009] In the above-mentioned method for producing a composite electrolyte membrane, for example, as shown in Fig. 8, a first electrolyte layer 11 and a second electrolyte layer 13 arranged on both sides of a composite layer 12 including a porous substrate are usually laminated to cover the porous substrate in order to impregnate the porous substrate with an electrolyte solution. When the strip of the electrolyte membrane sheet produced in this manner is supplied to the next processing step, for example, a step of laminating a catalyst layer, it may be slit-cut to adjust its widthwise length or to align both ends in the widthwise direction. For example, the strip is slit-cut at cutting positions s1 and s2 to produce a strip as shown in Fig. 9.

[0010] In the process of applying catalyst ink to the web shown in Figure 9, if the web is transported in a slightly meandering manner, the applied catalyst ink may spill out from the widthwise ends of the web, contaminating surrounding equipment such as guide rolls.

[0011] In addition, when the electrolyte membrane is relatively thick, the cut portions y1 and y2 of the slit-cut web may swell (FIG. 10), which may encourage the web to meander in its transport. When the web moves in a meandering manner, the sides of the wound roll may become uneven, or the catalyst ink may spill out.

[0012] In view of the above problems in the prior art, it is an object of the present invention to provide a strip of an electrolyte membrane sheet that can suppress, for example, the overflow or meandering of catalyst ink during the catalyst layer lamination step, and that can appropriately carry out subsequent steps without problems. Another object of the present invention is to provide a method for manufacturing a strip of an electrolyte membrane sheet that can appropriately carry out subsequent steps, such as a catalyst lamination step, without problems. [Means for solving the problem]

[0013] In order to achieve the above object, the strip of electrolyte membrane sheet of the present invention has the following configuration: That is, the strip of electrolyte membrane sheet is formed by laminating an electrolyte membrane on a strip-shaped base film, the electrolyte membrane having a thickness of 40 μm or more, the electrolyte membrane having, from the base film side, a first electrolyte layer containing a polymer electrolyte, a composite layer containing a porous base material and a polymer electrolyte, and a second electrolyte layer containing a polymer electrolyte, the both ends in the width direction of the base film, the first electrolyte layer, and the composite layer are at the same position, and the both ends in the width direction of the second electrolyte layer are located inside each of the both ends in the width direction of the base film, the first electrolyte layer, and the composite layer.

[0014] The method for producing a strip of an electrolyte membrane sheet of the present invention has the following configuration: (A) applying a first electrolyte solution containing a polymer electrolyte onto a strip-shaped base film having a widthwise length W0 so that the first electrolyte solution has a widthwise length W1 shorter than the length W0; (B) laminating a strip-shaped porous base material having a widthwise length W2 equal to or shorter than the length W1 to the coated surface of the first electrolyte solution in a wet state; (C) applying a second electrolyte solution containing a polymer electrolyte onto the porous base material so that the second electrolyte solution has a widthwise length W3 shorter than the length W2; and (D) drying the first electrolyte solution. This method for producing a strip precursor of an electrolyte membrane sheet whose widthwise lengths satisfy the relationship W0>W1≧W2>W3 is produced, and further includes a step (E) of slitting the base film, the first electrolyte layer, and the composite layer at positions outside both widthwise ends of the second electrolyte layer of the strip precursor of the electrolyte membrane sheet. Effect of the Invention

[0015] The belt-shaped electrolyte membrane sheet of the present invention prevents the catalyst ink from spilling out or meandering during the catalyst layer lamination process, and allows the next process to be carried out properly without any problems. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a schematic cross-sectional view in the width direction of one embodiment of a belt-shaped electrolyte membrane sheet of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view in the width direction of one embodiment of a belt-shaped precursor of an electrolyte membrane sheet of the present invention. [Diagram 3] FIG. 4 is a schematic cross-sectional view in the width direction of another embodiment of a belt-shaped precursor of an electrolyte membrane sheet of the present invention. [Figure 4] FIG. 1 is a side view showing a schematic configuration of an example of a manufacturing apparatus that can be used to manufacture a belt-shaped electrolyte membrane sheet of the present invention. [Diagram 5] FIG. 4 is a side view showing a schematic configuration of another example of a manufacturing apparatus that can be used to manufacture a belt-shaped electrolyte membrane sheet of the present invention. [Figure 6] FIG. 4 is a side view showing a schematic configuration of another example of a manufacturing apparatus that can be used to manufacture a belt-shaped electrolyte membrane sheet of the present invention. [Figure 7] FIG. 2 is a side view showing a schematic configuration of an example of a manufacturing apparatus that can be used in the step of laminating a catalyst layer. [Figure 8] FIG. 1 is a schematic cross-sectional view in the width direction of a strip of a conventional electrolyte membrane sheet. [Figure 9] FIG. 13 is a schematic cross-sectional view in the width direction of a conventional belt-shaped material after being cut into slits. [Figure 10] FIG. 10 is a partially enlarged view of the cut portion y1 in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The following describes in detail the embodiments of the present invention. However, the present invention is not limited to the following embodiments, and can be modified and implemented in various ways depending on the purpose and application of the present invention.

[0018] The strip of the electrolyte membrane sheet of the present invention is an electrolyte membrane having a thickness of 40 μm or more laminated on a strip of base film. The electrolyte membrane has, in order from the base film side, a first electrolyte layer containing a polymer electrolyte, a composite layer containing a porous base material and a polymer electrolyte, and a second electrolyte layer containing a polymer electrolyte. The electrolyte membrane is characterized in that both widthwise ends of the base film, the first electrolyte layer, and the composite layer are at the same position, and both widthwise ends of the second electrolyte layer are located inside both widthwise ends of the base film, the first electrolyte layer, and the composite layer.

[0019] Hereinafter, the strip of the electrolyte membrane sheet may be abbreviated to "strip." Furthermore, the base film, the first electrolyte layer, and the composite layer may be collectively referred to as "other components" with respect to the second electrolyte layer.

[0020] In the present invention, the expression "each of the two widthwise ends of the second electrolyte layer is located more inward than each of the two widthwise ends of the other components" means that each of the two widthwise ends of the second electrolyte layer is located closer to the widthwise center than each of the two widthwise ends of the other components.

[0021] 1 is a schematic cross-sectional view in the width direction of a strip according to the first embodiment of the present invention. Strip 101 has a first electrolyte layer 11, a composite layer 12, and a second electrolyte layer 13 on a base film 10 in this order. Ends A1 and A2 in the width direction of second electrolyte layer 13 are located closer to a center line C in the width direction than ends B1 and B2 in the width direction of other components (base film 10, first electrolyte layer 11, and composite layer 12), respectively. Here, the center line of the second electrolyte layer and the center lines of the other components are preferably in the same position, but may be shifted from each other. Details will be described later.

[0022] The strip according to the first embodiment can be manufactured, for example, by making the widthwise length of the substrate film, the widthwise length of the porous substrate, and the coating width of the first electrolyte layer the same, and making the coating width of the second electrolyte layer shorter than the widthwise lengths of the other components.

[0023] The strip according to the first embodiment can be produced, for example, by producing a strip precursor of an electrolyte membrane sheet (hereinafter sometimes abbreviated as strip precursor) as shown in Fig. 2 or 3, and slitting the strip precursor at cutting positions s1 and s2. The strip according to the first embodiment is preferably produced by slitting the strip precursor as described above. Details will be described later.

[0024] When the web according to the first embodiment is supplied to the next catalyst layer lamination step to laminate a catalyst layer on the second electrolyte layer of the web, it is effective to apply the catalyst ink so that the width of the catalyst layer is approximately the same as the width of the second electrolyte layer in terms of improving the yield. In this case, the catalyst ink is prevented from spilling out from the ends of the web by the fact that both ends of the second electrolyte layer are located inside both ends of the other components and there is a step between both ends of the second electrolyte layer and both ends of the other components.

[0025] From the above viewpoint, the end-to-end distance D1 between end A1 and end B1 and the end-to-end distance D2 between end A2 and end B2 are each preferably 1 mm or more, more preferably 2 mm or more, and particularly preferably 3 mm or more. That is, both ends of the second electrolyte layer are each preferably 1 mm or more inward from both ends of the other components, more preferably 2 mm or more inward, and particularly preferably 3 mm or more inward. Moreover, the end-to-end distances D1 and D2 are each preferably 20 mm or less, more preferably 15 mm or less, and particularly preferably 10 mm or less.

[0026] It is preferable that the end-to-end distances D1 and D2 are the same. This mode means that the center line of the second electrolyte layer and the center line of the other component are at the same position. The end-to-end distances D1 and D2 may be different within the above range. For example, D1 and D2 may differ by about 1 to 19 mm. This mode means that the center line of the second electrolyte layer and the center line of the other component are shifted, for example, by about 1 to 19 mm. In other words, the center line of the second electrolyte layer and the center line of the other component are allowed to shift within a range in which the end-to-end distances D1 and D2 can be ensured.

[0027] From the viewpoint of suppressing the overflow of the catalyst ink, the thickness of the second electrolyte layer is preferably relatively large, specifically, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. The upper limit of the thickness of the second electrolyte layer is about 70 μm. Furthermore, from the above viewpoint, the thickness ratio of the second electrolyte layer to the first electrolyte layer (thickness of the second electrolyte layer / thickness of the first electrolyte layer) is preferably 1.3 or more, more preferably 1.5 or more, even more preferably 2.0 or more, and particularly preferably 3.0 or more.

[0028] In addition, when the thickness of the second electrolyte layer is relatively large as described above, even if the slit-cut portions of other components bulge, the influence of the bulge is absorbed or mitigated by the thickness of the second electrolyte layer, and the meandering transport of the web is suppressed. By suppressing the meandering transport of the web, spillage of the catalyst ink is suppressed and the side surface of the roll is made uniform.

[0029] The width of the second electrolyte layer in the strip is determined appropriately according to the width required in the lamination process of the catalyst layer, and is generally about 500 to 2000 mm. The longitudinal length of the strip is generally about 100 to 3000 m.

[0030] [Method of manufacturing the belt-shaped material] As described above, the strip of the present invention can be produced by producing a strip precursor of an electrolyte membrane sheet as shown in Fig. 2 or 3 and slit-cutting the strip precursor at cutting positions s1 and s2. The form of the strip precursor will be specifically described below, but the present invention is not limited thereto.

[0031] 2 is a schematic cross-sectional view in the width direction of one embodiment of a strip precursor. The strip precursor 102 is formed by laminating a first electrolyte layer 11, a composite layer 12, and a second electrolyte layer 13 on a base film 10. The width direction center lines C of the respective components are approximately at the same position, and the width direction length of the second electrolyte layer 13 is the shortest.

[0032] The above-mentioned strip precursor is slit-cut at cutting positions s1 and s2, i.e., by cutting the other components (substrate film 10, first electrolyte layer 11 and composite layer 12) without cutting second electrolyte layer 13, a strip in the form shown in Figure 1 can be obtained.

[0033] The width direction center lines C of the above-mentioned components being approximately at the same position means that the width direction center lines of the components are allowed to deviate within a range in which the above-mentioned cutting positions s1 and s2 can be ensured. It is preferable that the width direction center lines of the components are at the same position.

[0034] In the configuration of Fig. 2, when the width direction length of the base film 10 is W0, the width direction length of the first electrolyte layer 11 is W1, the width direction length of the composite layer 12 is W2, and the width direction length of the second electrolyte layer 13 is W3, the relationship is "W0>W1>W2>W3", but the present invention is not limited thereto and may be, for example, the relationship of Fig. 3, that is, "W0>W1=W2>W3". In other words, the relationship of the width direction lengths of the components in the web-shaped precursor is preferably "W0>W1≧W2>W3".

[0035] In the above embodiment, from the viewpoint of smoothly performing the slit cutting, the difference between W2 and W3 (W2-W3) is preferably 10 mm or more, more preferably 15 mm or more, and particularly preferably 20 mm or more. On the other hand, from the viewpoint of the yield (reduction of waste) in the slit cutting, W2-W3 is preferably 200 mm or less, more preferably 150 mm or less, and particularly preferably 100 mm or less. The difference between W0 and W1 (W0-W1) is suitably about 10 to 250 mm, and preferably 20 to 200 mm. The difference between W1 and W2 (W1-W2) is suitably about 0 to 200 mm, and preferably 10 to 100 mm.

[0036] The width direction length of the second electrolyte layer in the strip precursor is appropriately determined, for example, according to the width direction length required in the lamination step of the catalyst layer, which is the next processing step. The width direction lengths of the other components (substrate film, first electrolyte layer, and composite layer) are appropriately determined according to the width direction length of the second electrolyte layer, further taking into consideration the above relationship.

[0037] As described above, the web of the present invention can be obtained by slit-cutting the web precursor. In this case, the second electrolyte layer is not cut. Therefore, even if the cut portion (B1 and B2 in FIG. 1) is raised, the effect of the raised portion is absorbed or mitigated by (the thickness of) the second electrolyte layer, and serpentine transport of the web is suppressed.

[0038] In addition, in the method for producing the strip of the present invention by slitting the strip precursor, the second electrolyte layer is not cut, so the slitting speed is significantly improved compared to the conventional method. From the viewpoint of improving the slitting speed, the thickness of the second electrolyte layer in the strip precursor is preferably relatively large, specifically, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. There is a preferred range for the combined thickness of the first electrolyte layer, composite layer, and second electrolyte layer in the strip. By making the thickness of the second electrolyte layer in the strip precursor thicker to some extent while taking into consideration that it is within that range, the thickness of the first electrolyte layer and composite layer to be cut becomes thinner, and the slitting speed is improved.

[0039] Furthermore, from the above viewpoints, the thickness ratio of the second electrolyte layer to the first electrolyte layer (thickness of the second electrolyte layer / thickness of the first electrolyte layer) is preferably 1.3 or more, more preferably 1.5 or more, even more preferably 2.0 or more, and particularly preferably 3.0 or more.

[0040] The slit cutting of the belt-shaped precursor can be performed using a known slit cutting device. As the slit cutting device, for example, a slit cutting device for slit cutting of belt-shaped materials such as optical film, polymer film, adhesive film, and protective film can be used. As the slit method, there are shear cut (sear cut) method, razor cut method, score cut method, etc., and the shear cut method is effective for slit cutting of the belt-shaped precursor having a relatively large film thickness as in the present invention.

[0041] [Method of manufacturing strip precursor] Next, the method for producing the strip precursor will be described in detail, but the present invention is not limited thereto. The strip precursor can be produced, for example, by carrying out the following steps in order: (A) applying a first electrolyte solution containing a polymer electrolyte onto a strip-shaped substrate film with a width direction length W0 so that the width direction length W1 is shorter than the length W0; (B) laminating a strip-shaped porous substrate with a width direction length W2 equal to or shorter than the length W1 onto the applied surface of the first electrolyte solution in a wet state; (C) applying a second electrolyte solution containing a polymer electrolyte onto the porous substrate so that the width direction length W3 is shorter than the length W2; and (D) drying.

[0042] In the above-mentioned production method, a drying step (F) can be provided between the steps (B) and (C), as will be described in detail later.

[0043] In the above manufacturing method, a first electrolyte layer is formed in step (A), a composite layer is formed in step (B), and a second electrolyte layer is formed in step (C). That is, the first electrolyte layer is formed with the first electrolyte solution, the porous substrate is bonded with the first electrolyte solution while the applied surface of the first electrolyte solution is in a wet state, thereby filling the porous substrate with the first electrolyte solution to form a composite layer, and the second electrolyte layer is formed with the second electrolyte solution.

[0044] The thickness of the first electrolyte layer and the second electrolyte layer can be adjusted by controlling the amount of the first electrolyte solution applied in step (A) and the amount of the second electrolyte solution applied in step (C). The amount of the first electrolyte solution applied is the total amount of the amount filled (impregnated) in the porous substrate and the amount forming the first electrolyte layer, and the amount can be determined from the porosity of the porous substrate, the design thickness of the electrolyte membrane, the solids concentration of the first electrolyte solution, etc., and can also be determined more precisely by simple tests or practical experience.

[0045] The above-mentioned manufacturing method is preferably carried out by a roll-to-roll method, in which a strip-shaped substrate film and a strip-shaped porous substrate are supplied by rolls, and the above-mentioned steps (A) to (D) and, if necessary, a drying step (F) are carried out, followed by winding into a roll.

[0046] Examples of the method for producing a belt-shaped precursor by the roll-to-roll method include the following first and second forms. That is, (First embodiment) The above steps (A), (B), (C), and (D) are carried out in one pass on one production line. (Second embodiment) After carrying out the above steps (A), (B) and (F), the mixture is temporarily wound into a roll, and steps (C) and (D) are carried out using this roll.

[0047] The first embodiment will be described in detail below. As a manufacturing apparatus capable of carrying out the first embodiment, the manufacturing apparatus shown in FIG.

[0048] In FIG. 4, a first electrolyte solution is applied to one side of a strip-shaped substrate film PF unwound from a roll unwinder 21 by a first coating device 22. Next, a strip-shaped porous substrate MS unwound from a supply roll 23 is bonded to the coated surface, and the strip-shaped porous substrate MS is impregnated with the first electrolyte solution. Here, a part of the first electrolyte solution is impregnated into the strip-shaped porous substrate MS, filling the pores of the strip-shaped porous substrate MS to form a composite layer. The remaining electrolyte solution that is not impregnated forms a first electrolyte layer. Therefore, the wet coating amount (wet thickness) of the first electrolyte solution is appropriately determined from the amount impregnated into the porous substrate and the design film thickness of the first electrolyte layer, as described above.

[0049] Next, the second electrolyte solution is applied to the strip-shaped porous substrate MS by the second application means 24, and then dried in a drying furnace 25 to produce a strip-shaped precursor 102. The produced strip-shaped precursor 102 is wound into a roll by a roll winder 26.

[0050] The coating device may be a slit die coater, a gravure coater, a bar coater, a roll coater, a doctor coater, a knife coater, a direct roll coater, a spray coater, a dip coater, a curtain coater, an extrusion coater, a spin coater, etc. Among these, a slit die coater is preferred as a coating method from the viewpoint of controlling the coating width with high accuracy.

[0051] The temperature of the drying oven is preferably from 50 to 200°C, more preferably from 60 to 170°C, and particularly preferably from 70 to 160°C.

[0052] The time from when the first electrolyte solution is applied to the strip-shaped substrate film PF until when the strip-shaped porous substrate MS is bonded thereto is not particularly limited as long as the wet state of the first electrolyte solution is maintained, but from the viewpoint of improving productivity and reducing equipment size, it is preferably within 5 minutes, more preferably within 3 minutes, and particularly preferably within 2 minutes. The lower limit is about 5 seconds.

[0053] The time from laminating the strip-shaped porous substrate MS to the surface of the strip-shaped substrate film PF coated with the first electrolyte solution until the second electrolyte solution is coated thereon, i.e., the impregnation time, is preferably 3 seconds or more, more preferably 5 seconds or more, and particularly preferably 10 seconds or more, from the viewpoint of sufficiently filling the pores of the strip-shaped porous substrate MS with the first electrolyte solution. From the viewpoint of improving productivity and reducing equipment size, the impregnation time is preferably 4 minutes or less, more preferably 3 minutes or less, and particularly preferably 2 minutes or less.

[0054] Also, a drying oven can be provided to dry the first electrolyte solution after the strip-shaped porous substrate MS is bonded to the surface of the strip-shaped substrate film PF coated with the first electrolyte solution and before the second electrolyte solution is coated. That is, a drying step (F) can be provided. However, in the first embodiment, it is preferable to coat the second electrolyte solution on the first electrolyte solution while it is wet, and then dry them all at once in the drying step (D). This allows for equipment reduction and improved productivity.

[0055] Next, a description will be given of the second embodiment. As a manufacturing apparatus capable of carrying out the second embodiment, the manufacturing apparatuses shown in Figs.

[0056] In Fig. 5, a first electrolyte solution is applied to one surface of a strip base material film PF unwound from a roll unwinder 31 by a first coater 32. Next, a strip-shaped porous base material MS unwound from a supply roll 33 is bonded to the coated surface, and the strip-shaped porous base material MS is impregnated with the first electrolyte solution. Next, the strip-shaped porous base material MS is dried in a drying furnace 35 to produce an intermediate product IMP (a strip-shaped base material film on which a first electrolyte layer and a composite layer are laminated). The produced intermediate product IMP is wound into a roll by a roll winder 36.

[0057] Next, a second electrolyte layer is laminated on the intermediate product IMP using the manufacturing apparatus of Fig. 6 to manufacture a strip precursor. In Fig. 6, a second electrolyte solution is applied by a second coating device 44 to the surface opposite to the base film of the intermediate product IMP unwound from a roll unwinder 41, and the surface is dried in a drying oven 45 to manufacture a strip precursor 102. The manufactured strip precursor 102 is wound into a roll by a roll winder 46.

[0058] When the belt-shaped precursor produced as described above needs to be subjected to an acid treatment for protonating the polymer electrolyte, in the production line of FIG. 4 or FIG. 6, a means for performing the acid treatment, for example, an acid treatment tank, a water washing tank and a drying furnace, can be installed between the drying furnace 25 and the roll winder 26 or between the drying furnace 45 and the roll winder 46, so that the acid treatment can be performed continuously following the production of the belt-shaped precursor. In addition, the acid treatment may be performed in a separate process after the production of the belt-shaped precursor. As the acid treatment device, for example, the devices described in JP 2011-194593 A and WO 2017 / 141710 A can be used.

[0059] The base film of the belt-shaped precursor may be replaced with another base film before being cut into slits, as will be described in detail later.

[0060] [Base film] In the web of the present invention, the base film and the electrolyte membrane are laminated in a releasable manner, and the base film is finally peeled off from the electrolyte membrane, for example, during the process of laminating catalyst layers on both sides of the electrolyte membrane of the web.

[0061] As the substrate film, a known polymer film can be used. Examples of the material of the polymer film include polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate, polyetherimide, polyphenylene sulfide, polyimide, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymers, and perfluoroalkoxy fluororesins. Among these, polyesters are preferred from the viewpoints of chemical resistance, heat resistance, and cost, and polyethylene terephthalate is particularly preferred. The substrate film is one that is ultimately peeled off, and may be subjected to a release treatment as necessary.

[0062] The thickness of the base film is preferably 150 μm or more, more preferably 175 μm or more, and particularly preferably 210 μm or more from the viewpoint of suppressing curling due to drying shrinkage of the electrolyte membrane, since the electrolyte membrane is relatively thick at 40 μm or more. On the other hand, from the viewpoint of reducing the load during slit cutting and suppressing an increase in the mass per unit length of the belt-like material, the thickness is preferably 500 μm or less, more preferably 400 μm or less, and particularly preferably 350 μm or less. Furthermore, from the above viewpoints, the thickness of the base film is within the range of 150 to 500 μm and is preferably 2.0 to 6.5 times the thickness of the electrolyte membrane, more preferably 2.5 to 5.0 times, and particularly preferably 3.0 to 4.5 times.

[0063] The substrate film used in the production of the strip precursor can be replaced with another substrate film before slitting. The thickness of the other substrate film is preferably 120 μm or less, more preferably 100 μm or less, and particularly preferably 80 μm or less. The thickness is preferably 20 μm or more, more preferably 30 μm or more, and particularly preferably 35 μm or more. The above-mentioned polymer film can be used as the other substrate film. The other substrate film can be subjected to a treatment, such as a heating treatment, a humidifying treatment, an anchoring treatment, or an adhesion treatment, for appropriately increasing the adhesion with the electrolyte membrane.

[0064] [Electrolyte membrane] The electrolyte membrane of the present invention has, in order from the substrate film side, a first electrolyte layer containing a polymer electrolyte, a composite layer containing a porous substrate and a polymer electrolyte, and a second electrolyte layer containing a polymer electrolyte. Here, the first electrolyte layer and the second electrolyte layer do not contain a porous substrate. The composite layer is formed by filling the pores of the porous substrate with the polymer electrolyte.

[0065] The electrolyte membrane of the present invention is preferably applied to a water electrolysis hydrogen generation device or an electrochemical hydrogen pump. In the water electrolysis hydrogen generation device or the electrochemical hydrogen pump, it is necessary to suppress reverse permeation of the generated hydrogen from the cathode to the anode, and therefore an electrolyte membrane with high hydrogen barrier properties is required. The electrolyte membrane of the present invention has a thickness of 40 μm or more and has relatively good hydrogen barrier properties.

[0066] From the viewpoint of improving the hydrogen barrier property, the thickness of the electrolyte membrane is preferably 50 μm or more, more preferably 60 μm or more, further preferably 70 μm or more, and particularly preferably 85 μm or more.

[0067] The hydrogen barrier property of the electrolyte membrane can be expressed by the hydrogen permeability in an atmosphere at 80° C. and a relative humidity of 90% (hereinafter simply referred to as "hydrogen permeability"). The hydrogen permeability of the electrolyte membrane in the present invention is 3.0×10 -7 cm 3 ·(cm 2 s cmHg) -1 It is preferable that the value is less than 2.0×10 -7 cm 3 ·(cm 2 s cmHg) -1 More preferably, it is 1.0×10 -7 cm 3 ·(cm 2 s cmHg) -1 It is particularly preferable that the hydrogen permeability is as follows: Here, the hydrogen permeability represents the amount of hydrogen permeating through the electrolyte membrane per unit area.

[0068] On the other hand, the thickness of the electrolyte membrane is preferably 250 μm or less, more preferably 200 μm or less, even more preferably 180 μm or less, and particularly preferably 150 μm or less, from the viewpoint of production efficiency and material cost. If the thickness of the electrolyte membrane exceeds 250 μm, the thickness of the base film needs to be made larger than necessary to suppress curling in the manufacturing process of the belt-like material, and the production efficiency may decrease due to an increase in material cost and an increase in the mass per unit length of the belt-like material. In addition, if the thickness of the electrolyte membrane is large, the load when cutting the slit may increase.

[0069] As described above, the thickness of the second electrolyte layer is preferably relatively large from the viewpoint of suppressing the catalyst ink from spilling out from the end of the web, suppressing meandering transport of the web, and improving the slit cutting speed of the web precursor, and specifically, the thickness is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. The upper limit is about 70 μm. Furthermore, from the above viewpoint, the thickness ratio of the second electrolyte layer to the first electrolyte layer (thickness of the second electrolyte layer / thickness of the first electrolyte layer) is preferably 1.3 or more, more preferably 1.5 or more, even more preferably 2.0 or more, and particularly preferably 3.0 or more.

[0070] From the viewpoint of increasing the mechanical strength of the electrolyte membrane and improving its durability, the thickness of the composite layer is preferably 20 μm or more, more preferably 25 μm or more, and particularly preferably 30 μm or more. On the other hand, from the viewpoint of proton conductivity, the thickness is preferably 47 μm or less, more preferably 45 μm or less, and particularly preferably 43 μm or less. The thickness ratio of the composite layer in the electrolyte membrane is preferably 10 to 90%, more preferably 20 to 80%, and particularly preferably 30 to 70%, with the thickness of the electrolyte membrane being 100%. Here, the thickness of the composite layer means the thickness of the porous substrate.

[0071] Examples of the form of the porous substrate constituting the composite layer include woven fabric, nonwoven fabric, microporous membrane, mesh fabric, etc. Examples of the material of the porous substrate include a hydrocarbon-based porous substrate mainly composed of a hydrocarbon-based polymer, a fluorine-based porous substrate mainly composed of a fluorine-based polymer, etc.

[0072] Hydrocarbon polymers include polyethylene (PE), polypropylene (PP), polystyrene (PS), polyacrylate, polymethacrylate, polyvinyl chloride (PVC), polyvinylidene chloride (PVdC), polyester, polycarbonate (PC), polysulfone (PSU), polyethersulfone (PES), polyphenylene oxide (PPO), polyarylene ether polymers, polyphenylene sulfide (PPS), polyphenylene sulfide sulfone, and polyparaphenylene (P PP), polyarylene polymers, polyarylene ketones, polyether ketones (PEK), polyether ether ketones (PEEK), polyether ketone ketones (PEKK), polyarylene phosphine oxides, polyether phosphine oxides, polybenzoxazoles (PBO), polybenzothiazoles (PBT), polybenzimidazoles (PBI), polyamides (PA), polyimides (PI), polyetherimides (PEI), and polyimide sulfones (PIS).

[0073] Examples of fluorine-based polymers include polytetrafluoroethylene (PTFE), polyhexafluoropropylene, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVdF), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy fluorine resin (PFA), and ethylene-chlorotrifluoroethylene copolymer (ECTFE).

[0074] The porous substrate serves to reinforce the strength of the electrolyte membrane, and from the viewpoint of reinforcing a relatively thick electrolyte membrane having a thickness of 40 μm or more, such as the electrolyte membrane of the present invention, a porous substrate having a relatively high strength is preferable, and from that viewpoint, a mesh fabric is preferable. Mesh fabrics have a relatively large fiber diameter and can be manufactured relatively easily with high strength, compared to porous substrates that have been conventionally and generally used in this field. As the material of the fiber constituting the mesh fabric, polyester, liquid crystal polyester, polyphenylene sulfide, polyether ketone, polyether ether ketone, and polyether ketone ketone are preferable.

[0075] The mesh fabric is used, for example, as a screen printing plate, and can be manufactured by a known manufacturing method. For example, it can be manufactured by referring to the manufacturing methods described in WO 2019 / 188960, WO 2019 / 146620, etc.

[0076] The polymer electrolytes contained in the first electrolyte layer, the composite layer, and the second electrolyte layer may be the same or different. Examples of the polymer electrolytes that are different include a case where the first electrolyte layer and the composite layer are the same and the second electrolyte layer is a different type.

[0077] As the polymer electrolyte, a known polymer electrolyte that constitutes an electrolyte membrane used in a fuel cell or a water electrolysis hydrogen generating device can be used. Examples of such polymer electrolytes include perfluoro-based polymers having ionic groups and hydrocarbon-based polymers having ionic groups. From the viewpoint of enhancing the hydrogen barrier property of the electrolyte membrane, hydrocarbon-based polymers having ionic groups are preferred.

[0078] The perfluoro-based polymer having an ionic group means a polymer in which most or all of the hydrogen atoms of the alkyl group and / or alkylene group in the polymer are replaced with fluorine atoms. Examples of the fluorine-based polymer electrolyte include perfluorocarbon sulfonic acid-based polymer, perfluorocarbon phosphonic acid-based polymer, trifluorostyrene sulfonic acid-based polymer, trifluorostyrene phosphonic acid-based polymer, ethylene tetrafluoroethylene-g-styrene sulfonic acid-based polymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride-perfluorocarbon sulfonic acid-based polymer, etc.

[0079] Among these, perfluorocarbon sulfonic acid polymers are preferred from the viewpoints of heat resistance and chemical stability. Examples of such polymers include commercially available products such as "Nafion" (registered trademark) (manufactured by Chemours), "Flemion" (registered trademark) (manufactured by AGC Corporation), and "Aciplex" (registered trademark) (manufactured by Asahi Kasei Corporation).

[0080] The hydrocarbon polymer having ionic group is more preferably an aromatic hydrocarbon polymer having aromatic ring in polymer main chain.Specific examples of aromatic hydrocarbon polymer include a polymer having a structure selected from polysulfone, polyethersulfone, polyphenylene oxide, polyarylene ether polymer, polyphenylene sulfide, polyphenylene sulfide sulfone, polyparaphenylene, polyarylene polymer, polyarylene ketone, polyether ketone, polyarylene phosphine oxide, polyether phosphine oxide, polybenzoxazole, polybenzothiazole, polybenzimidazole, polyamide, polyimide, polyetherimide, polyimide sulfone and aromatic ring in main chain. The polysulfone, polyethersulfone, polyetherketone, etc. mentioned here are general terms for structures having sulfone bonds, ether bonds, and ketone bonds in their molecular chains, and include polyetherketoneketone, polyetheretherketone, polyetheretherketoneketone, polyetherketoneetherketoneketone, polyetherketonesulfone, etc. The hydrocarbon skeleton may have a plurality of these structures. Among these, the most preferred aromatic hydrocarbon polymers are polymers having a polyetherketone skeleton, i.e., polyetherketone-based polymers. Polyetherketone-based polymers are preferred from the viewpoint of further enhancing the hydrogen barrier properties of the electrolyte membrane.

[0081] The ionic group used herein may preferably be one or more selected from the group consisting of a sulfonic acid group (-SO2(OH)), a sulfate group (-OSO2(OH)), a sulfonimide group (-SON2NHSO2R (R represents an organic group)), a phosphonic acid group (-PO(OH)2), a phosphoric acid group (-OPO(OH)2), a carboxylic acid group (-CO(OH)), and metal salts thereof. Among these, it is more preferable to have at least a sulfonic acid group, a sulfonimide group, a sulfate group, or a phosphonic acid group from the viewpoint of high proton conductivity, and it is most preferable to have at least a sulfonic acid group from the viewpoint of hydrolysis resistance.

[0082] When forming the electrolyte membrane, it is preferable to introduce these ionic groups as metal salts in order to reduce the inclusion of impurities due to the material of the coating device and the decomposition of the ionic groups due to heating. The metal that forms the metal salt may be any metal that can form a salt with the ionic group. From the viewpoint of cost and environmental load, Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, W, etc. are preferable, and among these, Li, Na, K, Ca, Sr, Ba are more preferable, and Li, Na, and K are even more preferable. The introduction of the ionic group into the electrolyte membrane may be performed by a method of introducing a metal salt or derivative of the ionic group into the polymer after polymerization, or may be performed by a method of introducing a metal salt of the ionic group into a monomer and then polymerizing the monomer.

[0083] When the ionic group is introduced as a metal salt, the electrolyte membrane can be treated with an acid (contacted with an acidic solution) after its formation to replace the metal salt with a proton and convert it into an ionic group. As the acid treatment method, a known method can be used.

[0084] The electrolyte membrane may further contain additives such as a crosslinking agent and a crystallization nucleating agent, a plasticizer, a stabilizer, a release agent, an antioxidant, a radical scavenger, and inorganic fine particles that are used in ordinary polymer compounds, for the purposes of improving mechanical strength, improving the thermal stability of ionic groups, improving water resistance, improving solvent resistance, improving radical resistance, improving the coatability of a coating liquid, and improving storage stability.

[0085] [Catalyst layer stacking process] The strip of the present invention is supplied to the next processing step, for example, a catalyst layer lamination step, where a catalyst layer is laminated on the electrolyte membrane of the strip. As a method for laminating the catalyst layer, a transfer method, a coating method, and a combination of a transfer method and a coating method are generally known, but here, the coating method is taken as an example for explanation. Figure 7 is a side view showing a schematic configuration of an example of a manufacturing apparatus that can be used in the catalyst layer lamination step.

[0086] 7, a catalyst ink is applied to the surface of the second electrolyte layer of the web 101 unwound from an unwinder roll 51 by an applicator 52, and the web is dried in a drying oven 53 to form a catalyst layer, thereby producing a catalyst-coated electrolyte membrane CCM. The produced CCM is wound into a roll by a roll winder 56.

[0087] In such a catalyst layer lamination process, the strip of the present invention has both ends of the second electrolyte layer located inside both ends of the other components, and there is a step between both ends of the second electrolyte layer and both ends of the other components, which prevents the applied catalyst ink from spilling out from the widthwise ends and prevents contamination of surrounding members such as guide rolls. Furthermore, the strip of the present invention is transported without meandering, which further prevents the applied catalyst ink from spilling out from the widthwise ends. Furthermore, because the strip is transported without meandering, the side surface of the rolled material wound by the roll winder 56 is uniform.

[0088] Even when the catalyst layer is transferred by a roll-to-roll method using a catalyst layer transfer sheet, the belt-shaped article of the present invention is transported without meandering, so that the catalyst layer transfer sheet can be properly attached.

[0089] In addition, after a catalyst layer is laminated on the second electrolyte layer of the strip, the base film of the strip is peeled off to expose the first electrolyte layer, and a catalyst layer is laminated on this first electrolyte layer by the same coating method or transfer method as above, to obtain an electrolyte membrane with a catalyst layer in which the catalyst layer is laminated on both sides of the electrolyte membrane.

[0090] [Example of application] The electrolyte membrane in the web of the present invention can be used for electrochemical applications, such as fuel cells, redox flow batteries, water electrolysis hydrogen generators, and electrochemical hydrogen compression devices. Among these, water electrolysis hydrogen generators are most preferred. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. Various measurement and evaluation methods are as follows.

[0092] (1) Measurement of polymer molecular weight The number average molecular weight and weight average molecular weight of the polymer solution were measured by GPC. Tosoh Corporation's HLC-8022GPC was used as an integrated device of an ultraviolet detector and a differential refractometer. Two Tosoh Corporation's TSK gel SuperHM-H (inner diameter 6.0 mm, length 15 cm) were used as GPC columns. Measurements were performed in N-methyl-2-pyrrolidone solvent (N-methyl-2-pyrrolidone solvent containing 10 mmol / L lithium bromide) at a flow rate of 0.2 mL / min, and the number average molecular weight and weight average molecular weight were calculated in terms of standard polystyrene.

[0093] (2) Thickness measurement The cross section of the electrolyte membrane sheet was observed with a scanning electron microscope (SEM) under the following conditions, and the thickness of each sheet was measured from the obtained images. Equipment: Field emission scanning electron microscope (FE-SEM) S-4800 (Hitachi High-Technologies) Accelerating voltage: 2.0 kV Pretreatment: Cross-sectional samples prepared by the BIB method were coated with Pt and then measured. BIB method: Cross-sectional specimen preparation equipment using an argon ion beam. A shielding plate is placed directly above the specimen, and a broad argon ion beam is irradiated from above to etch the specimen, creating an observation and analysis surface (cross section).

[0094] (3) Slit cutting speed The belt-shaped precursors of the Examples and Comparative Examples were cut into slits using a shear-cut type slitting device, and the maximum cutting speed at which no cutting defects such as tearing occurred was determined.

[0095] (4) Observation of guide roll contamination and meandering transport of strips in the catalyst layer lamination process Using the manufacturing apparatus shown in Fig. 7, the following catalyst ink was applied to the second electrolyte layer of the web of the examples and comparative examples, dried, and an electrolyte membrane with a catalyst layer was manufactured and wound up. At this time, the guide roll was visually observed to see if it was contaminated by the adhesion of the catalyst ink. Also, it was visually observed to see if the web was meandering during transport.

[0096] <Catalyst ink> Catalyst particles: 10 parts by mass of platinum catalyst-supported carbon particles TEC10E50E (platinum support rate 50% by mass) manufactured by Tanaka Kikinzoku Kogyo Co., Ltd. Fluorine-based polymer electrolyte: 5 parts by mass of "Nafion" (registered trademark) D2020 manufactured by Chemours Corporation (a dispersion liquid with a mass ratio of electrolyte, water, and 1-propanol of 20:34:46) converted into solid content Solvent: A mixture of water and 1-propyl alcohol in a mass ratio of 4:6 The above catalyst particles and polymer electrolyte were dispersed in a solvent using a bead mill to prepare a catalyst ink with a solid content concentration of 10% by mass.

[0097] [Synthesis of polyether block copolymers] <Synthesis of block copolymer b1> [Synthesis Example 1] (Synthesis of 2,2-bis(4-hydroxyphenyl)-1,3-dioxolane (K-DHBP) represented by the following general formula (G1)) In a 500mL flask equipped with a stirrer, a thermometer and a distillation tube, 49.5g of 4,4'-dihydroxybenzophenone, 134g of ethylene glycol, 96.9g of trimethyl orthoformate and 0.50g of p-toluenesulfonic acid monohydrate were charged and dissolved. Then, the mixture was stirred at 78-82°C for 2 hours. Furthermore, the internal temperature was gradually raised to 120°C, and the mixture was heated until the distillation of methyl formate, methanol and trimethyl orthoformate completely stopped. After cooling the reaction solution to room temperature, the reaction solution was diluted with ethyl acetate, the organic layer was washed with 100mL of a 5% aqueous potassium carbonate solution and separated, and the solvent was distilled off. 80mL of dichloromethane was added to the residue to precipitate crystals, which were then filtered and dried to obtain 52.0g of 2,2-bis(4-hydroxyphenyl)-1,3-dioxolane. GC analysis of the crystals revealed that they consisted of 99.8% 2,2-bis(4-hydroxyphenyl)-1,3-dioxolane and 0.2% 4,4'-dihydroxybenzophenone.

[0098] [ka]

[0099] [Synthesis Example 2] (Synthesis of disodium-3,3'-disulfonate-4,4'-difluorobenzophenone represented by the following general formula (G2)) 109.1g of 4,4'-difluorobenzophenone (Aldrich reagent) was reacted in 150mL of fuming sulfuric acid (50% SO3) (Wako Pure Chemical Industries, Ltd. reagent) at 100℃ for 10 hours. After that, it was gradually poured into a large amount of water, neutralized with NaOH, and then 200g of table salt (NaCl) was added to precipitate the synthesized product. The resulting precipitate was filtered and recrystallized with an ethanol aqueous solution to obtain disodium-3,3'-disulfonate-4,4'-difluorobenzophenone represented by the following chemical formula (G2). The purity was 99.3%.

[0100] [ka]

[0101] [Synthesis Example 3] (Synthesis of nonionic oligomer a1 represented by the following general formula (G3)) In a 2,000 mL SUS polymerization apparatus equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 16.59 g of potassium carbonate (Aldrich reagent, 120 mmol), 25.83 g (100 mmol) of K-DHBP obtained in Synthesis Example 1, and 20.3 g of 4,4'-difluorobenzophenone (Aldrich reagent, 93 mmol) were placed. After nitrogen replacement, 300 mL of N-methylpyrrolidone (NMP) and 100 mL of toluene were added, dehydrated at 160 ° C, heated to remove toluene, and polymerization was carried out at 180 ° C for 1 hour. Reprecipitation purification was carried out with a large amount of methanol to obtain a terminal hydroxyl body of nonionic oligomer a1. The number average molecular weight of the terminal hydroxyl body of this nonionic oligomer a1 was 10,000.

[0102] In a 500mL three-neck flask equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 1.1g of potassium carbonate (Aldrich reagent, 8mmol) and 20.0g (2mmol) of the terminal hydroxyl form of the nonionic oligomer a1 were placed. After replacing the atmosphere in the apparatus with nitrogen, 100mL of NMP and 30mL of cyclohexane were added, and the mixture was dehydrated at 100°C, and then heated to remove the cyclohexane. Furthermore, 4.0g of decafluorobiphenyl (Aldrich reagent, 12mmol) was added, and the reaction was carried out at 105°C for 1 hour. Reprecipitation purification was carried out with a large amount of isopropyl alcohol to obtain a nonionic oligomer a1 (terminal: fluoro group) represented by the following general formula (G3). The number average molecular weight was 11,000.

[0103] [ka]

[0104] [Synthesis Example 4] (Synthesis of ionic oligomer a2 represented by the following general formula (G4)) In a 2,000mL SUS polymerization apparatus equipped with a stirrer, nitrogen inlet tube, and Dean-Stark trap, 27.6g of potassium carbonate (Aldrich reagent, 200mmol), 12.9g (50mmol) of K-DHBP obtained in Synthesis Example 1, 9.3g of 4,4'-biphenol (Aldrich reagent, 50mmol), 40.1g (95mmol) of disodium-3,3'-disulfonate-4,4'-difluorobenzophenone obtained in Synthesis Example 2, and 17.9g of 18-crown-6 (Wako Pure Chemical Industries, Ltd., 82mmol) were placed, and after nitrogen replacement, 300mL of NMP and 100mL of toluene were added, dehydration was performed at 150°C, and the temperature was raised to remove toluene, and polymerization was performed at 170°C for 6 hours. Reprecipitation purification was performed with a large amount of isopropyl alcohol to obtain an ionic oligomer a2 (terminal: OM group) represented by the following general formula (G4). The number average molecular weight was 21,000. In addition, in the formula (G4), M represents Na or K. Furthermore, n represents a positive integer.

[0105] [ka]

[0106] [Synthesis Example 5] (Synthesis of block copolymer b1) In a 2,000mL SUS polymerization apparatus equipped with a stirrer, nitrogen inlet tube, and Dean-Stark trap, 0.56g of potassium carbonate (Aldrich reagent, 4mmol) and 21g (1mmol) of oligomer a2 containing an ionic group (terminal: OM group) were placed and substituted with nitrogen. Then, 100mL of NMP and 30mL of cyclohexane were added, and after dehydration at 100°C, the temperature was raised to remove the cyclohexane, and 11g (1mmol) of oligomer a1' (terminal: fluoro group) not containing an ionic group was placed and reacted at 105°C for 24 hours. Block copolymer b1 was obtained by reprecipitation purification in a large amount of isopropyl alcohol. The weight average molecular weight was 350,000.

[0107] [Porous substrate (mesh fabric)] A porous substrate made of liquid crystal polyester fiber produced in Production Example 1 of WO 2019 / 188960 was used. This porous substrate had a fiber diameter of 25 μm, a gauze thickness of 35 μm, an opening of 52 μm, and an opening area (OPA) of 45%.

[0108] [Preparation of electrolyte solution p1] 20 parts by mass of block copolymer b1 was added to 80 parts by mass of NMP and stirred with a stirrer at 20,000 rpm for 1 hour to prepare a transparent solution with a polymer concentration of 20% by mass. This solution was pressure filtered with a glass fiber filter to prepare an electrolyte solution p1.

[0109] [Example 1] <Production of Strip Precursor> Using the manufacturing apparatus of FIG. 4, the electrolyte solution p1 was applied to the substrate film (PET film), the porous substrate was bonded and impregnated, and the electrolyte solution p1 was further applied to the porous substrate and dried to produce the strip precursor 1, which was then wound into a roll. The length of the roll of the strip precursor 1 was 500 m. The width direction length and thickness (dry thickness) of each component are as follows. The center lines of each component in the width direction are located at the same position. (Width) -Width of base film W0: 900mm Width of first electrolyte layer W1: 800 mm Composite layer (porous substrate) width W2: 700mm · Width direction length of second electrolyte layer W3: 600 mm (Thickness) · Thickness of base film: 300μm Thickness of the first electrolyte layer: 10μm Composite layer (porous substrate) thickness: 35μm Thickness of the second electrolyte layer: 40μm - Total thickness of electrolyte membrane: 85μm.

[0110] <Manufacture of belt-shaped material> The above-mentioned belt-like material precursor 1 was cut at cutting positions s1 and s2 as shown in FIG. 2 by a shear-cut type slit cutting device to obtain a belt-like material 1. The maximum cutting speed was 10 m / min. The width direction length of the second electrolyte layer of the obtained belt-like material 1 was 600 mm, the width direction length of the other components was 610 mm, and the end-to-end distances D1 and D2 were each 5 mm. The center lines of the components in the width direction were at the same position.

[0111] <Observation of meandering transport of strips and guide roll contamination in the catalyst layer lamination process> The catalyst ink was applied over a coating width of 600 mm. There was no contamination of the guide rolls. Also, there was no meandering of the web.

[0112] [Example 2] <Production of Strip Precursor> A belt-shaped precursor 2 was produced in the same manner as in Example 1, except that the thickness was changed as follows. (Thickness) - Thickness of base film: 300μm Thickness of the first electrolyte layer: 25μm Composite layer (porous substrate) thickness: 35μm Thickness of second electrolyte layer: 25μm - Total thickness of electrolyte membrane: 85μm.

[0113] <Manufacture of belt-shaped material> The above-mentioned belt-like material precursor 2 was cut at cutting positions s1 and s2 as shown in FIG. 2 by a shear-cut type slit cutting device to obtain a belt-like material 2. The maximum cutting speed was 8 m / min. The width direction length of the second electrolyte layer of the obtained belt-like material 2 was 600 mm, the width direction length of the other components was 610 mm, and the end-to-end distances D1 and D2 were each 5 mm. The center lines of the components in the width direction were at the same position.

[0114] <Observation of meandering transport of strips and guide roll contamination in the catalyst layer lamination process> The catalyst ink was applied over a coating width of 600 mm. There was no contamination of the guide rolls. Also, there was no meandering of the web.

[0115] [Comparative Example 1] <Production of Strip Precursor> A belt-shaped precursor 3 was produced in the same manner as in Example 2, except that the width direction length of each component was changed as follows. The center lines of each component in the width direction were located at the same position. (Width) -Width of base film W0: 900mm Width of first electrolyte layer W1: 700 mm Composite layer (porous substrate) width W2: 650mm · Width direction length W3 of second electrolyte layer: 700 mm.

[0116] <Manufacture of belt-shaped material> The above-mentioned belt-like material precursor 3 was cut at cutting positions s1 and s2 as shown in FIG. 8 by a shear-cut type slit cutting device to obtain a belt-like material 3. The maximum cutting speed was 4 m / min. The width direction lengths of the second electrolyte layer and other components of the obtained belt-like material 2 were both 610 mm, and the end-to-end distances D1 and D2 were each 0 mm. The center lines of the components in the width direction were at the same position.

[0117] <Observation of meandering transport of strips and guide roll contamination in the catalyst layer lamination process> The catalyst ink was applied over a coating width of 600 mm. Contamination of the guide roll and meandering transport of the web were observed. [Explanation of symbols]

[0118] 10. Base film 11 First electrolyte layer 12 composite layers 13 Second electrolyte layer 21, 23, 31, 33, 41, 51 Roll unwinder 22, 32 First coating device 24, 44 Second coating device 25, 35, 45, 55 Drying oven 26, 36, 46 56 Roll winder 52 Catalyst ink application device 101 Electrolyte membrane sheet strip 102 Precursor of electrolyte membrane sheet strip PF Strip-shaped base film MS Strip-shaped porous substrate IMP intermediate product (a first electrolyte layer and a composite layer laminated on a strip-shaped substrate film) CCM Electrolyte membrane with catalyst layer A1, A2 Ends of the second electrolyte layer B1, B2 Ends of other components D1, D2 distance between ends C Center line in width direction s1, s2 cutting position y1, y2 cut section

Claims

1. 1. A strip of an electrolyte membrane sheet comprising an electrolyte membrane laminated on a strip-shaped base film, the electrolyte membrane having a thickness of 40 μm or more, the electrolyte membrane having, from the base film side, a first electrolyte layer containing a polymer electrolyte, a composite layer containing a porous base material and a polymer electrolyte, and a second electrolyte layer containing a polymer electrolyte, the base film, the first electrolyte layer, and the composite layer having both widthwise ends at the same position, and the second electrolyte layer having both widthwise ends located inside each of the base film, the first electrolyte layer, and the composite layer.

2. 2. The electrolyte membrane sheet strip according to claim 1, wherein both widthwise ends of the second electrolyte layer are located 1 mm or more inward from both widthwise ends of the base film, the first electrolyte layer and the composite layer.

3. 3. The electrolyte membrane sheet strip according to claim 1, wherein the second electrolyte layer has a thickness of 10 [mu]m or more.

4. 4. The electrolyte membrane sheet strip according to claim 1, wherein the porous substrate is a woven mesh fabric.

5. A method for producing a belt-shaped electrolyte membrane sheet according to any one of claims 1 to 4, comprising the steps of: 0 A first electrolyte solution containing a polymer electrolyte is applied to a strip-shaped substrate film having a length W 0 The width direction length W is shorter than 1 a step (A) of applying the first electrolyte solution to the applied surface so as to have the length W 1 A width direction length W that is equal to or shorter than 2 a step (B) of applying a second electrolyte solution containing a polymer electrolyte to the porous substrate in a length W 2 The width direction length W is shorter than 3 The coating step (C) and the drying step (D) are carried out in this order so that the relationship of the width direction length is W 0 >W 1 ≧W 2 >W 3 and further comprising a step (E) of slit-cutting the base film, the first electrolyte layer and the composite layer at outer positions of both widthwise ends of the second electrolyte layer of the electrolyte membrane sheet strip precursor.

Citation Information

Patent Citations

  • Method of producing polymer electrolyte membrane and production apparatus of polymer electrolyte membrane

    JP2015076201A

  • Method of manufacturing reinforcement type electrolyte film

    JP2016149329A

  • Polymer electrolyte membrane and manufacturing method therefor

    JP2016216826A

  • Manufacturing method for manufacturing composite electrolyte membrane

    JP2018092759A

  • Method for manufacturing electrolyte membrane

    JP2018113140A